Measures in curbing poor compliance to building control regulation among renovated terrace houses - Mohamed Sabri, Bibi Khairani; Ujang, Norsidah; Muhammad Arif, Afida Mastura; Aripin, Srazali (Emerald Group Publishing Ltd., 2017)
Purpose: The purpose of this study is to explore measures taken by local authorities in curbing poor compliance among renovated terrace houses in the state of Selangor, Malaysia. Design/methodology/approach: A qualitative methodology was selected in the data collection and analysis of the study. Seven local authority officers from seven selected local authorities were invited to participate in a face-to-face interview session to share their experience. A focus group was conducted for the purpose of confirming the validity of the data collected during the interview session. The focus group consisted of 32 officers in charge of building control enforcement invited from 11 local authorities within Selangor State. Findings: The results show that collecting revenue rather than ensuring compliance is the main objective among the authorities responsible for enforcing the regulations. There are four common tools adopted to penalize the offenders, which are compounds, demolition, prosecution and court orders, with a mix of opinions on their objective achievement. Major obstacles identified in the implementation of the enforcement task are low staffing capacity in monitoring and inspection, difficulties in preparing investigation paper and problems carrying out the demolition of illegal extensions. Originality/value: The study uncovers obstacles to enforcing regulations on home renovations. The findings contribute toward improving the enforcement practices of local building control authorities.